PEMBUKTIAN TERBALIK PADA TINDAK PIDANA PENCUCIAN UANG - Sahuri Lasmadi; Elly Sudarti (Refleksi Hukum: Jurnal Ilmu Hukum, 2021)
This research is motivated by the difficulty of the proving process in the crime of money laundering in which mechanism to reverse the burden of proof is used during examination in court. This research is normative legal research, using a statutory, conceptual, and case approach. From the results of this research, it can be concluded: (1) Reverse evidence is applied to the assets of the defendant, both for active money laundering (Article 3 and Article 4) and passive money laundering (Article 5). However, the concept of reverse proof is not clearly and explicitly explained in the PP TPPU Law, confusing its implementation in court. (2) If the defendant succeeds in proving, the assets are still under the control of the accused and his heirs. On the other hand, if the defendant fails to prove, the defendant's assets will be confiscated by the State after a binding court decision is released.